(untitled) (Journal of Philosophy Culture and Political Science, 2021)
This paper examines communication strategies of an indigenously founded religion with 5 million followers in Vietnam, Caodaism. Blending Orthodox Taoism from China, Indianized Champa with Siva worship, and French Catholicism, Caodaism emerged as a new religion, initially linked to the peasantry and civil movements in southern Vietnam, with a military of its own. Spread by refugees, a missionary ideal, and digital media Caodaism is a social movement and a religion known in many nations for its sacred images, symbols, colors, and Holy Scripture. Caodaism leaders have tried to meet new demands of the followers’ network and strengthen its focus while disseminating its beliefs and practices globally. Indeed, the leaders of the religion have and continue to make significant efforts to internationalize its representation through websites, translations of books and scriptures, attending international conferences, and socializing with other religions. Due to limited funding, Caodaists make use of YouTube videos to disseminate their teachings. Of the 60 official videos on Cao Dai TV, 47 clips cover news on the operation and special activities of Caodaism. The newscast intends to spread the Caodai faith to both established Caodaists and converts. Events such as the reconstruction of a temple in a remote county and the anniversary of the inauguration of the religion became news, with hopes to show whatever progress Caodaists are making toward upholding their beliefs. The channel can be seen as an effort to interact with Caodaists all over the world. Although a locally born religion with ample influence by Southern Vietnamese culture, Caodaism and its mediated messages are oriented towards such omnipresent values as self-improvement, solidarity, enlightenment and liberation from suffering. Key words: Caodaism, content analysis, media spectacle, religious study.